Simplified hybrid algorithms for pressure wire interrogation exploiting advantages of a baseline and contrast Pd/Pa ratio indexes to predict stenosis significance: Insight from the SPARE multicenter prospective study. Issue 6 (23rd April 2018) - Cerrato, E.; Tomassini, F.; Salinas, P.; Pavani, M.; Conrotto, F.; Echavarria‐Pinto, M.; Macaya, F.; Quadri, G.; D'Ascenzo, F.; Quirós, Alicia; Varbella, F.; Escaned, J.
Abstract: Background: Simplification of functional stenosis assessment with pressure guidewires may facilitate adoption of physiology‐guided revascularization. An important step in this regard is the avoidance of hyperemic agents, required for fractional flow reserve (FFR) calculation. We evaluate the merits of a hybrid algorithms that combines the translesional pressure ratio (Pd/Pa) obtained at rest, after contrast medium injection (cFFR) and after adenosine administration (FFR). Methods and Results: Eighty‐six patients with 108 de novo intermediate coronary stenoses were included in this prospective, multicenter study. Using prespecified cut‐off values that correctly identified stenosis with a 95% of agreement (<0.89 and >0.96 for Pd/Pa; <0.84 and > 0.87 for cFFR) we tested the efficiency of three different multi‐step strategies combining the three indices to classify stenosis severity, using FFR‐only measurement as reference. All three different hybrid algorithms (Pd/Pa‐FFR; cFFR‐FFR; Pd/Pa‐cFFR‐FFR) have more than 95% of agreement with FFR. Yet, the novel Pd/Pa‐cFFR‐FFR hybrid strategy demonstrated the best performance, avoiding the need of adenosine and medium contrast in 90% and 48% of cases, respectively. Conclusions: A hybrid Pd/Pa‐cFFR‐FFR decision‐making algorithm could be an alternative and valuable strategy to increase the adoption of a physiology‐guided PCI using conventional pressure guidewires and consoles.